Systematic Review and Meta-Analysis on the Implementation of “Brigada Eskwela” in Philippine Public Schools - S. Digo, Gerry; O. Tarraya, Hilger; F. Evangelista, Mary Anne; E. Mape, Jellian; D. Sano, Sheryll; B. Payno, Joseph; S. Polo, Celeste; M. Rejuso, Robert (ASEAN Journal of Education, 2023)
This study assessed the “Brigada Eskwela” implementation among Philippine public schools. Specifically, this paper identified and analyzed the strengths, weaknesses, opportunities, and threats of “Brigada Eskwela” as a method to recommend strategies to improve and sustain its implementation. The primary sources of data are research articles about the implementation of “Brigada Eskwela” which were collected from different online resources by conducting a systematic review and meta-analysis. The proposed strategies were developed through SWOT analysis and are aligned with the vision, mission, core values of the Department of Education to improve and sustain the “Brigada Eskwela” implementation in Philippine public schools. The results revealed that the “Brigada Eskwela” program of the Department of Education is beneficial for schools and its driving forces are already present within the school. These include the leadership capability of the heads of school, the availability of workforces such as teaching and nonteaching personnel, parents, and volunteers, support from stakeholders, and innovations to improve the school. As to weaknesses, the findings revealed inadequate school resources, proper planning mechanisms, and effective communication of the implementation plan. There is also a need to improve the preparation and presentation of reports and make them more substantial. In terms of opportunities, it is evident that parents, students, the community, and other stakeholders including private individuals or organizations are responsive to the call for volunteerism and partnerships. Threats include the location of the school, availability of private individuals or organizations, access to stakeholders, low economic status of parents and community, and stakeholders’ negative attitude towards the program.